Oxidative stress-mediated apoptosis induced by ethanolic mango seed extract in cultured estrogen receptor-positive breast cancer MCF-7 Cells - Al-Shwyeh, Hussah Abdullah; Abdulkarim , Sabo Mohammed; Rasedee, Abdullah; Mirghani, Mohamed Elwathig Saeed (MDPI, 2015)
Breast cancer has become a global health issue requiring huge expenditures for care and treatment of patients. There is a need to discover newer cost-effective alternatives for current therapeutic regimes. Mango kernel is a waste product with potential as a source of anti-cancer phytochemicals, especially since it is non-toxic towards normal breast cell lines at concentrations for which it induces cell death in breast cancer cells. In this study, the anti-cancer effect of mango kernel extract was determined on estrogen receptor-positive human breast carcinoma (MCF-7) cells. The MCF-7 cells were cultured and treated with 5, 10 and 50 μg/mL of mango kernel extract for 12 and 24 h. In response to treatment, there were time- and dose-dependent increases in oxidative stress markers and pro-apoptotic factors; Bcl-2-like protein 4 (BAX), p53, cytochrome c and caspases (7, 8 and 9) in the MCF-7 cells treated with the extract. At the same time, there were decreases in pro-survival markers (Bcl-2 and glutathione) as the result of the treatments. The changes induced in the MCF-7 cells by mango kernel extract treatment suggest that the extract can induce cancer cell apoptosis, likely via the activation of oxidative stress. These findings need to be evaluated further to determine whether mango kernel extract can be developed as an anti-breast cancer agent.